LISTENING STRATEGIES USED BY THE FOURTH SEMESTER STUDENTS AT ACADEMIC LISTENING CLASS - Enjelina Like; Ika Paramitha Lantu; Sherliane Trisye Poai (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
The Objective of this research is to find out the strategies used by the fourth semester students at English Education Study Program of Sintuwu Maroso University. This research is a descriptive qualitative that used questionnaire, interview and documentation as the instruments to collect data. Theory used in this research are the theory of learning strategies from Chamot and O’Malley. After analyzing the obtained data, it is found that the fourth semester students used cognitive, metacognitive and socio-affective strategies to help them in learning academic listening. The findings showed that the students used cognitive, metacognitive and socio-affective strategies based on the questionnaire result but on the interview result the students used cognitive strategies. Based on the result, it can concluded the students used the strategies to help them in learning academic listening.